Diversity and composition of ferns and lycophytes in a fragmented landscape in Ecuadorian Amazonia - Moulatlet Gabriel Massaine; Riaño Karolina; Rodrigues Flávio R.O.; Meneses Pablo; Zuquim Gabriela (Instituto de Pesquisas Jardim Botanico do Rio de Janeiro, 2025)
Tropical forests have been subjected to increasing deforestation, leading to severe habitat loss and fragmentation of the landscape. Studies of various plant groups-indicate alteration in species diversity and assemblage composition in response to these impacts. How theses impacts affect ferns and lycophytes, however, is less well known. In this study we evaluate the effects of habitat loss and fragmentation on ferns and lycophytes in lowland non-inundated forests in Ecuadorian Amazonia. We obtained assemblage information from thirteen plots located in gradients of habitat loss and fragmentation (as measured by the landscape fragmentation index: fragindex) and used community and diversity indices to evaluate species responses. We found 3,824 individuals of 55 species. The plot with the highest fragindex value (more than 20% of habitat loss and fragmentation) had the lowest diversity, but the highest diversity was found in plots with fragindex values from 12% to 21% of habitat loss and fragmentation rather than in the landscapes without deforestation. Although community composition varied along the fragindex gradient, species turnover was not significantly related to this index. These results suggest that changes in the landscape caused by deforestation alter the availability of habitats, consequently affecting the distribution patterns of ferns and lycophytes. © 2023 Instituto de Pesquisas Jardim Botanico do Rio de Janeiro. All rights reserved.